The determination and procedure transformation of the ionosphere parameters with GNSS-observations - Yankiv-Vitkovska, L.; Savchuk, S.; Pauchok, V. (Видавництво Львівської політехніки, 2015)
Purpose. Solutions to the problems of coordinate-time provision based on continuous GNSS-observations is based on the processing of large data sets of code and phase measurements. One of the possible additional options for conducting this study is computation of the numerical characteristics of the ionospheric impact on the signals distribution from the satellites - the values of the total electron density (TEC). These characteristics reflect the dynamics of the atmosphere ionization that is important in terms of monitoring the circumterrestrial space. Arrays of the STEC and VTEC values are so significant that there is actual problem of preparing ionosphere parameters for their further analysis and use. To solve this problem, we proposed a technique based on a set of programs that convert VTEC data measurements to a format suitable for the analysis. Methods. TEC indicators can be computed due to the automated processing of files with GNSS-observation results from each satellite for an individual station. Processing algorithm is based on the use of the computed code and phase pseudo-distances in the receiver and calibration coefficients. This algorithm allows you to get the TEC values in two ways: a) according to the phase measurements only and having used the results of phase ambiguities in the network as a whole beforehand and b) according to the code measurements only that were smoothed beforehand. In one-station algorithm, TEC value is determined for an individual station according to the measurements of all satellites during the period of 24 hours. For converting STEC (along the satellite-receiver beam) in vertical VTEC, a vertical single-layer model of the ionosphere is used. This model presupposes that all the electrons are concentrated in a thin layer that is located at a certain height above the Earth's surface. Results. For determination of the spatial TEC distribution, an algorithm of processing GPS measurements for multiple-stations was implemented using a network of active reference stations in the Western Ukraine. The network consists of 17 stations that work under control of specialized software in real time to provide the RTK services to the wide range of users interested in geodetic areas. Scientific novelty. The program for calculation of the STEC and VTEC values was written. This program uses already known subprograms, that are used for reading RINEX files, detection, estimation, and elimination of cyclical phasejumps, which arise in the process of measurements, subprograms that we developed for smoothing code measurements, receiving differential corrections at the time, calculation of the horizontal coordinates of the satellite on the observational station, direct calculation of TEC and subsequent storage of the received data in the new file on the server of Lviv Polytechnic National University. The entire program was compiled for the Linux operating system and automated for use with observational data of permanent IGS station SULP. The research resulted in improvement of an algorithm for determining the parameters of the ionosphere, development and implementation of software for regular computing of the ionospheric parameters - slant (STEC) and vertical (VTEC) values of total electron content, and proving of its practical use on SULP station. Practical significance. Calculation of the parametres of ionosphere at fixed moments of observation for each GNSS- satellite. Мета. Розв’язування задач координатно-часового забезпечення на основі безперервних GNSS- спостережень базується на опрацюванні великих масивів даних кодових та фазових вимірювань. Одним із можливих додаткових варіантів такого опрацювання є обчислення числових характеристик впливу іоносфери на поширення сигналів від супутників - значень загальної концентрації електронів ТЕС. Ці характеристики відображають динаміку іонізації атмосфери, що важливо з погляду моніторингу навколоземного простору. Масиви значень ТЕС (STEC і VTEC) такі значні, що виникає актуальна задача підготовлення даних параметрів іоносфери для їхнього подальшого аналізу та використання. Для розв’язання цієї задачі ми пропонуємо методику, що грунтується на комплексі програм, які перетворюють дані вимірювання VTEC до форми, зручної для аналізу. Методика. Обчислення ТЕС відбувається внаслідок автоматизованого опрацювання файлів GNSS-спостережень для окремої станції по кожному супутнику. Алгоритм опрацювання базується на використанні виміряних кодових і фазових псевдовідстаней у приймачі та калібрувальних коефіцієнтів. Він дає змогу отримувати значення ТЕС у двох варіантах: а) лише за фазовими вимірюваннями, попередньо використавши розв’язки фазових неоднозначностей у мережі загалом та б) лише за кодовими вимірюваннями, попередньо згладивши їх. Після чого кодові псевдовідстані згладжуються підібраними на основі апроксимованих змін фази у часі відповідними функціями. В одностанційному варіанті визначаються значення ТЕС над окремою станцією за вимірюваннями всіх супутників на 24-годинному інтервалі. Для перерахунку STEC у вертикальний VTEC використовується одношарова модель іоносфери. Результати. Для отримання просторового розподілу ТЕС був реалізований алгоритм багатостанційної обробки GPS вимірів з використанням мережі активних референцних станцій Західного регіону України. Мережа складається із 17 станцій, які працюють під управлінням спеціалізованого програмного забезпечення у режимі реального часу для забезпечення послугами RTK широкого кола користувачів геодезичного спрямування. Наукова новизна: Розроблено програму для обчислення похилих STEC і вертикальних VTEC значень ТЕС, що використовуються для читання RINEX файлів, виявлення, оцінки та усунення циклічних фазових стрибків, що виникають під час вимірювань; підпрограми для згладження кодових вимірювань, отримання диференційних поправок на момент обчислення, обчислення горизонтальних координат супутника на станцію спостережень, безпосереднє обчислення ТЕС і подальшого зберігання отриманих даних VTEC і ТЕС в нових файлах на сервері Львівської політехніки. Вся програма була скомпільована для операційної системи Linux і доведена до автоматизованого використання з даними спостережень перманентної IGS станції SULP. Практична значущість. Обчислення параметрів іоносфери на фіксовані моменти спостереження від всіх доступних GNSS-супутників. Цель. Решение задач координатно-временного обеспечения на основе непрерывных GNSS-наблюдений базируется на обработке больших массивов данных кодовых и фазовых измерений. Одним из возможных дополнительных вариантов такой обработки является вычисление числовых характеристик влияния ионосферы на распространение сигналов от спутников - значений обшей концентрации электронов ТЕС. Эти характеристики отражают динамику ионизации атмосферы, что важно с точки зрения мониторинга околоземного пространства. Массивы значений ТЕС (STC и VTEC) так значительны, что возникает актуальная задача подготовка данных параметров ионосферы для их дальнейшего анализа и использования. Для решения этой задачи нами предлагается методика, базирующаяся на комплексе программ, которые преобразуют данные измерения VTEC к форме, удобной для анализа. Методика. Вычисление ТЕС происходит вследствие автоматизированной обработки файлов GNSS-наблюдений для отдельной станции по каждому спутнику. Алгоритм обработки базируется на использовании измеренных кодовых и фазовых псевдорасстояний в приемнике и калибровочных коэффициентов. Он позволяет получать значение ТЕС в двух вариантах: а) только за фазовыми измерениями, предварительно использовав решения фазовых неоднозначностей в сети в целом и б) только по кодовым измерениям, предварительно сгладив их. После чего кодовые псевдорасстояния сглаживаются подобранными на основе аппроксимированных изменений фазы во времени соответствующими функциями. В одностанцийном варианте определяются значения ТЕС над отдельной станцией по измерениям всех спутников на 24-часовом интервале. Для пересчета STEC в вертикальный VTEC используется однослойная модель ионосферы. Результаты. Для получения пространственного распределения ТЕС был реализован алгоритм многостанпионные обработки GPS- измерений с использованием сети активных референцных станций Западного региона Украины. Сеть состоит из 17 станций, которые работают под управлением специализированного программного обеспечения в режиме реального времени для обеспечения услугами RTK широкого круга пользователей геодезического направления. Научная новизна: Разработана программа для вычисления наклонных STEC и вертикальных VTEC значений ТЕС, используемых для чтения RINEX-файлов, выявления, оценки и устранения циклических фазовых скачков, возникающих в процессе измерений; подпрограммы для сглаживания кодовых измерений, получения дифференциальных поправок на момент вычисления, вычисления горизонтальных координат спутника на станциюнаблюдений, непосредственное вычисление ТЕС и дальнейшего хранения полученных данных и в новых файлах на сервере Львовской политехники. Вся программа была скомпилирована для операционной системы Linux и доведена до автоматизированного использования с данными наблюдений перманентной IGS станции SULP. Практическая значимость. Вычисление параметров ионосферы на фиксированные моменты наблюдения от всех доступных GNSS спутников.
Визначення параметрів іоносфери і методика їх перетворення з GNSS-спостережень
Определение параметров ионосферы и методика их преобразования с GNSS-наблюдений
Keywords: GNSS-measurements; ionosphere; ionospheric parameters; smoothing; spline approximation; GNSS-виміри; іоносфера; іоносферні параметри; згладжування; сплайн; GNSS-измерения; ионосфера; ионосферные параметры; сглаживание; сплайн